Information System Design for Material and Interim Product Store Department in an Indonesian Small Shipyard - Firmansyah, Mohammad Rizal; Asri, Syamsul; Fachruddin, Farianto; Wahyuddin, Wahyuddin; Clausthaldi, Fadhil Rizki; Alwi, Muhammad Rusydi; Haris, Muhammad Rezky Pratama; Khalis, Muhammad Risqan (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
The ship production process at shipyards involves complex and critical information that must be managed effectively to ensure timely project completion. Ambiguities or delays in information exchange among departments can result in project setbacks and increased costs, which reduce revenue and undermine competitiveness. To address this, each department involved in ship construction must adopt an information system that ensures efficient communication both internally and across departments. Key information includes requirements for raw materials, consumables, workforce, production facilities, equipment, and the production methods used at each stage—factors that directly affect cost allocation. In many small shipyards across Indonesia, information is still processed and shared manually, leading to significant delays and inefficiencies. There is an urgent need for a digital information system tailored to the specific functions of each department and designed to facilitate smooth interdepartmental interaction. However, prior to system development, it is essential to understand and map the information flows within and between departments. This study focuses on the materials and interim products department, a critical part of the ship production process. The aim is to identify and map the internal information flows of this department and propose a suitable digital information system for implementation in small-scale Indonesian shipyards. By doing so, the research contributes to improving production efficiency and supports digital transformation in the domestic shipbuilding industry.